Neoconservative strategies, gender and family in the 2022 electoral race - Maria Mantovani , Denise; Mariano dos Santos , Rayani; Cazallas do Nascimento , Thayane (Revista Estudos Feministas, 2023)
Brazil has faced a process of intensification of neoconservatism in the recent period with attacks on discussions and policies aimed at combating gender inequalities, as well as an expansion of religious mobilization in the political space. In 2022, the electoral dispute became polarized between the current president, Jair Bolsonaro, and former president Luiz Inácio Lula da Silva. Two aspects stand out: women’s rejection of Bolsonaro and the dispute among evangelical voters. Based on the analysis of electoral programs aired on open television channels, this article intends to observe how Bolsonaro and Lula’s electoral advertisements in the second round mobilize arguments around gender issues, family and religiosity in the light of feminist critical perspectives.